Energize job retention: Energy management strategies as a component of business retention and expansion programs. Issue 2 (15th March 2017) - Bowen-Ellzey, Nancy; Romich, Eric
Abstract: To address the barriers to the growth or retention of existing businesses, economic development practitioners commonly use a business retention and expansion (BRE) program. Businesses frequently cite the cost of doing business, including energy costs, as a barrier to growth. Implementing energy management systems are an excellent way for businesses to reduce and stabilize energy costs, allowing them to remain profitable and grow. Businesses that make the decision to invest in a cost-saving energy system are also making the decision to retain the business for at least the life of the project. Energy projects, in large part because of project longevity, are as good as BR&E "gold" in the retention of existing businesses.